A new species and new record of Chinoperla Zwick, 1980 (Plecoptera: Perlidae) from Yunnan Province, China - Yan, Yanhua; Wang, Jie; Wang, Mingju; Li, Weihai (Zootaxa, 2022)
Two species of the genus Chinoperla Zwick, 1980 are reported with color images from Yunnan Province of southwestern China, including one described as new to science: C. longispina Yan & Li, sp. nov., and a new provincial record: C. gorohovi Sivec & Stark, 2010.